The Effect of Garlic Powder on Enterobius vermicularis infection - AL-BAYATI, Ahmed Fu’ad; AL-NAJAR, sabah Abbas (Journal of the Faculty of Medicine Baghdad, 2005)
Summary: Background: Enterobius vermicularis causes infection in different age groups , but specially in small ages . It is well known that parasitic infection in most middle eastern countries is common among them is Entrobius vermicularis , in which 11% is in school- children & 14% in pre-school children . In Iraq several studies on the prevalence of Enterobiasis in different age groups & from different areas were reported. Aim of study: This study was conducted to look for the therapeutic efficacy of garlic powder against Enterobiasis and the recurrence of this infection in many individuals to be compared with the drugs of choice that is a single dose, 100 mg of mebendazole tablets. Patients <6 Methods: One hundred and sixty patients were included in this study mostly were children, suffering from the clinical manifestation of Enterobiasis and confirmed by scotch tape slide method for identification. Those patients are divided into 2 groups: - 1- first group including 80 patients treated by garlic capsule 400 mg 2- Second group included 80 patients treated by mebendazole tablets lOOmg. Results: We found that the highest incidence of Enterobiasis was in females 56.9% than males 43.1 % simultaneously age group 6 to 10 years showed the highest rate of infection. Our results showed that the typical dose of garlic capsule to eradicate Enterobius vermicularis 100% is one capsule twice-daily for three consecutive days. All patients and control group were followed up to 6 months and it has been noticed that patients who received garlic therapy had no recurrence, except three patients as compared with twenty-five patients of control group. Conclusion: Our study had proved the therapeutic efficacy of garlic powder against Enterobiasis and we recommended it to be used instead of mebendazole.